(3TQM GdEjVGMs - (3CHh HcQ YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfjs; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSj, CHh Ydj,J (B377 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh Ydi (B: (3HGH Gdfai HdG GdeVGQY ddeVGa s
(3BNQgG (B:s
(3CYfi Cf GdQgHhf hGdQMehJ heG CTHg Pdc eUGOQ cdgG hdjS TF efgG HLejY acPG jLH Cf jchf GdWGZhf aGYQag ce GdLRA GdKGfi ef TQM GdTjN GdLQLGfi , hjJdhg ai GdKGdK HGH LeY GdJcSjQ s
(3HChdgG bQGAI dTQa GdOjf CHh eMeO GdaVd Hf GdMSf Hf YHO Gddg Ydi CHh GdMSf Ydi Hf CHj WGdH QhM Hf CMeO GdfgQhGfi cJH gPG HNWg UMI GdbQGAI ai QHjY GdBNQ SfI (B587s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs